2015
DOI: 10.1002/anie.201506273
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Asymmetric Dehydrogenative Cross‐Coupling between Two CH Groups Catalyzed by a Chiral‐at‐Metal Rhodium Complex

Abstract: A sustainable C-C bond formation is merged with the catalytic asymmetric generation of one or two stereocenters. The introduced catalytic asymmetric cross-coupling of two C(sp3)-H groups with molecular oxygen as the oxidant profits from the oxidative robustness of a chiral-at-metal rhodium(III) catalyst and exploits an autoxidation mechanism or visible-light photosensitized oxidation. In the latter case, the catalyst serves a dual function, namely as a chiral Lewis acid for catalyzing enantioselective enolate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(48 citation statements)
references
References 64 publications
0
48
0
Order By: Relevance
“…In addition to redox-neutral C–H functionalizations, Meggers has demonstrated that enantioselective net oxidative α-amino alkylations with α-silylamines 153 or tertiary amines 154 can be readily accomplished (Scheme 32c). In both of these protocols, oxygen is the terminal oxidant and in situ generation of an iminium ion is followed by trapping with the Lewis acid-bound enolate.…”
Section: Photoredox Lewis Acid Catalysismentioning
confidence: 99%
“…In addition to redox-neutral C–H functionalizations, Meggers has demonstrated that enantioselective net oxidative α-amino alkylations with α-silylamines 153 or tertiary amines 154 can be readily accomplished (Scheme 32c). In both of these protocols, oxygen is the terminal oxidant and in situ generation of an iminium ion is followed by trapping with the Lewis acid-bound enolate.…”
Section: Photoredox Lewis Acid Catalysismentioning
confidence: 99%
“…Moreover, by using blue LED, Meggers, Gong and coworkers have reported that ΔΛ-RhO1 could be used as photosentizer for the CÀ H activation of alkyl amine substrates to generate the key intermediate III (Scheme 36). [50] Then, III could react with the rhodium-enolate complex II following the same mechanism described above (Scheme 36) to make the aerobic asymmetric Csp 3 À H cross coupling reaction (Scheme 37). Concerning the substrate scope, despite moderate yields, good enantioselectivities with high substituent tolerances for the aromatic groups on the amine or the acyl-imidazole were observed.…”
Section: Asymmetric Photoredox Catalysis (α-Radicals)mentioning
confidence: 99%
“…[4] Avariety of asymmetric transformations have been successfully achievedw ith high catalytic efficiency and enantioselectivity. [5][6][7][8] To obtain the enantiopure chiral-at-metalc atalysts, a chiral auxiliary ligand is introduced to allow resolution of the initially formed diastereomericp recursor complexes by standard flash chromatography. [9] Subsequently,t he acid labile auxiliary ligand is cleaved off to provide the enantiopure chiral-atmetal catalyst.…”
Section: Introductionmentioning
confidence: 99%